2015
DOI: 10.3126/kumj.v12i3.13708
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes of Transurethral Resection of the Prostate in Benign Prostatic Hyperplasia Comparing Prostate Size of more than 80 Grams to Prostate Size less than 80 Grams

Abstract: Background

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
12
2
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 21 publications
2
12
2
1
Order By: Relevance
“…The complications were comparable to Jordan experience, 11 however, the hospital stay was less as compared to 6.08 ±4.01 and 4.80 ±1.47 days in the previous study comparing small and large prostate TURP. 9 Transient incontinence for first three months was encountered in more than one-third (38%) patients after TURP in Romanian cohort, 10 however only 22% in our study had this problem which improved significantly by 1 year of follow-up. On long term follow-up, the large prostate cohort had a significant relief (p=0.000) in lower urinary tract symptoms, with IPSS scores at 1 year post-surgery comparable in both the groups (p=0.421).…”
Section: Discussioncontrasting
confidence: 46%
See 3 more Smart Citations
“…The complications were comparable to Jordan experience, 11 however, the hospital stay was less as compared to 6.08 ±4.01 and 4.80 ±1.47 days in the previous study comparing small and large prostate TURP. 9 Transient incontinence for first three months was encountered in more than one-third (38%) patients after TURP in Romanian cohort, 10 however only 22% in our study had this problem which improved significantly by 1 year of follow-up. On long term follow-up, the large prostate cohort had a significant relief (p=0.000) in lower urinary tract symptoms, with IPSS scores at 1 year post-surgery comparable in both the groups (p=0.421).…”
Section: Discussioncontrasting
confidence: 46%
“…11 The study from Jordan had reported 72 ±6.2 minutes resection time for sizes more than 80 grams, 11 and the series from Kathmandu had comparatively very high resection time for both small and large prostate groups (110 ±15 vs 90±20). 9 Longer resection time in large prostate volume subjects of our study meant more bleeding and greater fall in hemoglobin (p=0.016), and larger raw bleeding area requiring prolonged post-op catheterization till hemostasis was achieved (3.58 ±0.84 vs 2.15 ±0.36, p=0.000). The fall in hemoglobin in the large prostate group in our study (0.92 ±0.58 mg/dl) was less than that encountered by Al-Hammouri et al (3.2 ±0.6 mg/ dl) in same size group.…”
Section: Discussionmentioning
confidence: 69%
See 2 more Smart Citations
“…Surgical treatments (transurethral resection of the prostate or open surgery) are used for treatment in the event of failed medical management [4]. Transurethral resection of the prostate (TURP) is considered the gold standard of treatment for men with prostate volumes of 30–80 ml, and it is also appropriate for those with prostate volumes > 80 ml [1, 5]. However, the complications of TURP include sexual dysfunction, retrograde ejaculation, postoperative hemorrhage, continent urinary retention, TURP syndrome and urinary stricture [6, 7].…”
Section: Introductionmentioning
confidence: 99%